THERMAL-HYDRAULIC ANALYSIS OF SMR WITH NATURALLY CIRCULATING PRIMARY SYSTEM DURING LOSS OF FEED WATER ACCIDENT - Susyadi (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2016)
Small Modular Reactors (SMRs) have several advantages over conventional large reactors. With integral and simplified design, application of natural laws for safety system, and lower capital cost this reactor is very suitable to be deployed in Indonesia. One of SMR designs being developed implements natural driving force for its primary cooling system. With such innovative approach, it is important to understand safety implication of the design for all operating circumstances. One of conditions need to be investigated is the loss of feed-water (LoFW) accident. In this study, thermal-hydraulic performance of the SMR with naturally circulating primary system during LoFW accident is analysed. The purpose is to investigate the characteristics of flow in primary system during the accident and to clarify whether the naturally circulating coolant is adequately capable to transfer the heat from core in order to maintain safe condition under considered scenario. The method used is by representing the reactor system into RELAP5 code generic models and performing numerical simulation. Calculation result shows that following the initiating event and reactor trip, primary system flow becomes significantly fluctuated and coolant temperature decreases gradually, while in secondary side steam quality descends into saturated. The primary flow slows down from 711 kg/s to 263 kg/s and starts to increase up again at t= 46 seconds. At the slowest point, fuel centerline and coolant temperatures were 565 K and 554 K, showing that temperatures of the fuel and coolant are still below its design limit and saturation point, respectively. This fact reveals that throughout transient the two main thermal hydraulic parameters stay in acceptable values so it could be concluded that under LoFW accident the SMR with naturally circulating primary system is in safe condition. Keywords: SMR, , , ,